PENERAPAN PERTANGGUNGJAWABAN PIDANA BADAN USAHA (KORPORASI) DALAM KETENTUAN YANG BERKAITAN DENGAN HUKUM LINGKUNGAN - Herlina Manullang (Universitas Borneo Tarakan, 2019)
AbstractMany things in human life has been affected by a legal entity (corporation), if the positive effect is certainly no need to worry, but just a lot of influence has been harmful to individuals and society at large. Criminal Code as the legal basis in criminal legislation only mentions that a criminal act can only be done by an individual (naturlijk person) is not a business entity (corporation). This has led to the growth of various laws outside the Criminal Code that recognizes the position of a business entity (corporation) as subjects of criminal law, especially in the provision of environmental law. Recognition notch business entities (corporations) as the subject of criminal law in environmental law provisions certainly result in the criminal responsibility.Keyword: Legal Entity, environmental Law, Criminal